Occurrence of neonatal hypothermia and associated risk factors among low birth weight (LBW) infants in Accra, Ghana - John Pellegrino; Mufaro Kanyangarara; Babbel Agbinko-Djobalar; Prince Gyebi Owusu; Kwame Sarfo Sakyi; Peter Baffoe; Adziri Sackey; Isabel Sagoe-Moses; Robin B Dail (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Neonatal hypothermia is a prominent issue in low-resource settings. Preterm and low birth weight (LBW) infants are at increased risk for developing hypothermia. If left untreated, hypothermia can lead to hypoxia, sepsis, hypoglycemia, apnea, and poor weight gain in neonates, contributing to neonatal morbidity and mortality. Identifying risk factors for neonatal hypothermia is important, especially in low-resource settings, where the burden of neonatal mortality is highest. The study sought to describe the distribution of neonatal hypothermia and examine risk factors associated with neonatal hypothermia among LBW infants admitted to Korle-Bu Teaching Hospital in Accra, Ghana. # Methods Infants in the neonatal intensive care unit (NICU) at Korle-Bu Teaching Hospital, who were less than 28 days old, weighing less than \<2,500 grams, and clinically stable, were enrolled. Infants of mothers under 18 years old and those expected to be discharged within 24 hours were excluded from the study. A standardized questionnaire was administered to collect information on the mother, infant, pregnancy, and birth characteristics. Axillary temperature readings were taken every 4 hours over a 24-hour monitoring period and during hypothermic events detected by the continuous temperature monitoring bracelet. Univariate and multivariate linear regression analyses with generalized estimating equations were used to examine risk factors associated with temperature. # Results Of the 254 infants included in the analysis, 42.1% were male, 49.6% were very LBW (\<1,500 grams), and 94.1% were preterm (\<37 weeks). Of the 1,948 temperature readings, 44.5% were hypothermic (\<36.5^o^C). Hypothermia occurred in 85.8% of infants during the 24-hour monitoring period. Multivariate linear regression demonstrated that being very LBW, having no skin-to-skin contact immediately after birth, not being wrapped or treated in an incubator at the time of temperature, and mixed feeding (compared to exclusive breastfeeding) were associated with lower neonatal temperatures. # Conclusions Neonatal hypothermia was common among infants admitted to the NICU. The findings highlight the importance of thermal practices such as wrapping, exclusive breastfeeding and skin-to-skin contact. Increased education to promote thermal care is needed.